COMPARATIVE STUDY OF GENDER REASSIGMENT IN INDONESIA IN THE PERSPECTIVE OF POSITIVE LAW AND ISLAMIC LAW - Rahmawati, Fita; Hidayah, Astika Nurul (UNTAG Law Review, 2023)
Gender and sex are two different things. Sex is synonymous with the difference in physical form between women and men. While gender refers more to the characteristics, roles, functions, status, and responsibilities. Some people feel that their gender and sex are not in harmony, so they decide to change their sex by having sex reassignment surgery, and ask for a court order. This is certainly a pro and con for Indonesian society, which is predominantly Muslim, especially if a Muslim changes his or her gender. This research aims to analyze the regulation of sex reassignment in Positive Law and Islamic Law in Indonesia. This research uses the normative juridical method, namely with statutory documents, and other literature studies related to this research. The results of the study show that in Indonesia there is no specific regulation regarding sex reassignment due to sex reassignment surgery, but judges usually use jurisprudence and use the provisions of Article 56 Number 24 of 2013 concerning Population Administration, while in the view of Islamic Law the law of sex reassignment surgery is prohibited, unless the surgery is for health purposes then there are some scholars who allow it.